Historic heritage conservation planning through the lens of logotherapy the case of Capas, Tarlac - Elane, Mary Margaret F. (College of Architecture, University of the Philippines Diliman, 2018)
This study explores the theory of logotherapy, a meaning-centered theory, as an approach in heritage landscape planning. More specifically, its purpose is to establish meaning as the basis for planning the conservation of historic heritage landscapes. Through a case study performed on Capas, Tarlac, the researcher looked into possible sources of meaning- design foundations, design intentions, and perceptions of the landscape. The landscape patterns of Capas revealed that it is founded on and driven by natural and rational belief systems. The planning approaches of the authorities revealed that the Municipality is envisioned to be the tourism capital of Tarlac. And the individual perceptions of the locals revealed that they have an intimate bond with nature and history. By integrating the three dimensions of meaning, the researcher determined the heritage asset of Capas. The main heritage asset of Capas is its history being the terminal point of the Bataan Death March during the Japanese occupation period. This asset is physically manifested in the various Death March sites and markers in Capas, particularly the Capas National Shrine. In seeking to integrate the tangible and intangible historical asset of Capas, the concept of everyday heroism was applied. Heroism is not only the meaning embedded in the heroic deeds of the soldiers who suffered the Death March, but also the meaning that the local community of Capas can aspire for. The historic heritage conservation plan for Capas will involve the people in rediscovering history, celebrating culture, and preserving the environment. In this manner, the heroes are not only the soldiers who suffered for the sake of the country, but also the local members of the community of Capas who have the task of safeguarding their heritage.